2017
DOI: 10.1213/ane.0000000000002058
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Production, Impact, and Scientific Collaboration on Difficult Airway Through the Web of Science and Scopus (1981–2013)

Abstract: We found a greater increase over time in the number of difficult airway manuscripts than for anesthesiology research overall. We found that collaboration between authors increases their impact, and that an increase in collaboration increases citation rates. Publishing in English and in certain journals, and collaborating with certain authors and institutions, increases the visibility of manuscripts published on this subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Our results present the most complete picture of airway management research and some of our findings are in contrast with other published work. García‐Aroca et al recently conducted a bibliometric assessment of difficult airway research, and similarly found a year‐on‐year increase in the number of publications, as well as further support that Anaesthesia as a journal is a publishing leader in this field . However, they reported a much lower annual publication rate than our results revealed, and this was likely due to a much narrower search strategy than we have used in this current study .…”
Section: Discussionsupporting
confidence: 79%
“…Our results present the most complete picture of airway management research and some of our findings are in contrast with other published work. García‐Aroca et al recently conducted a bibliometric assessment of difficult airway research, and similarly found a year‐on‐year increase in the number of publications, as well as further support that Anaesthesia as a journal is a publishing leader in this field . However, they reported a much lower annual publication rate than our results revealed, and this was likely due to a much narrower search strategy than we have used in this current study .…”
Section: Discussionsupporting
confidence: 79%
“…However, further analysis using multivariate analysis model did not show significant relationships at different subgroups. While Figg et al 86 reported that there is a correlation between the number of authors and the number of times an article is cited by other researchers, the work of García-Aroca et al 87 showed that publishing in English in certain journals and collaborating with certain authors and institutes increase the visibility of the manuscripts published on the subject. Therefore, it is the quality of collaboration rather than the absolute number of these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The question that can be raised in this regard is: are we expecting an increase in number of citations as the number of authors or the number institutes involved increased? The work of García-Aroca et al 78 shows that collaboration between authors increases their impact and increases citation rates. However, they showed that publishing in English in certain journals and collaborating with certain authors and institutes increase the visibility of the manuscripts published on the subject.…”
Section: Discussionmentioning
confidence: 99%